Computational and Experimental Analysis Reveals the Arachidonic Acid Metabolite 20-Hydroxyeicosatetraenoic Acid is a Novel Ligand of the Na/K-ATPase - Faleel, Dhilhani (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.